The New Institutional Economics, Business Associations, and Development - SCHNEIDER,BEN ROSS (2000)
ABSTRACT With the demise of development economics in the 1970s, the academic discipline of economics had little specific theorizing on development to offer practioners and proffered instead universal, liberal nostrums of free trade and free markets (Wing, 1990). These universal prescriptions evolved into the first catalogued Washington consensus in the 1980s on the urgency of market-oriented reforms in developing countries (Williamson, 1990). In the 1990s, a new connection formed between an emerging institutionalist subfield in economics and the next consensus in Washington after the first generation of market-oriented reforms. The opening of the third annual meetings of the International Society for New Institutional Economics (ISNIE) at World Bank headquarters in Washington, D.C. in September 1999 symbolized this new connection.